2006
DOI: 10.1136/vr.158.2.51
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thermophilic Campylobacter species in cats and dogs in two animal shelters in Ireland

Abstract: Rectal swabs or faecal samples for the isolation of Campylobacter species were taken from 120 dogs and cats in an animal shelter in which only one kitten showed signs of gastrointestinal disease, and rectal swabs were taken from 46 dogs, 22 of which showed signs of gastrointestinal disease, in another shelter. At the first shelter, the swabs from 24 of 47 dogs (51.1 per cent) and 36 of 48 cats (75 per cent) yielded a Campylobacter species. The rate of isolation was significantly higher from dogs and cats less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 25 publications
4
64
2
1
Order By: Relevance
“…(2006, 2009b) noticed in dogs and cats with diarrhoea, especially in those under 6 months, high prevalence of C.  spp. The differences between diseased and healthy animals as well as between the age groups were largely insignificant.…”
Section: Discussionmentioning
confidence: 98%
“…(2006, 2009b) noticed in dogs and cats with diarrhoea, especially in those under 6 months, high prevalence of C.  spp. The differences between diseased and healthy animals as well as between the age groups were largely insignificant.…”
Section: Discussionmentioning
confidence: 98%
“…These percentages may be higher in animals purchased in kennels. Prevalence of thermophilic Campylobacter species in samples of rectal swabs from dogs and cats varied with age group, with or without sign of gastroenteritis in two animal shelters in Ireland, showed that the isolation rate was higher in dogs and cats less than six months and significantly higher in dogs compared to cats (ACKE et al, 2006). Tenkate and Stafflord (2001) stated that about 6% of cases of human campylobacteriosis were transmitted from pets.…”
Section: Campylobacter In Dogsmentioning
confidence: 99%
“…In general, dogs < 1 year of age are at the greatest risk for acquiring an infectious disease. 45,78,80,[94][95][96][97][98] This increased risk is attributable to various factors, including inadequate vaccination, waning maternal antibodies, exposure to novel pathogens, and behaviors (eg, chewing of fomites, close play with other dogs, and mouthing activity) that increase the likelihood of direct and indirect pathogen spread. As mentioned in the vaccination recommendations, ensuring that young dogs have received their core vaccination series will assist in reducing these risks.…”
Section: Additional Exclusionary Measuresmentioning
confidence: 99%
“…These attributes include but are not limited to the setting (eg, indoor or outdoor), 43 geographic characteristics, 44 ages involved, 45 degree of dog-to-dog and dog-to-person contact, 46 and infection prevention methods used. 47 Setting and infectious disease expertise is required to effectively evaluate or identify specific risks inherent in each situation.…”
Section: General Recommendationsmentioning
confidence: 99%